Cytogenetic analysis of antimutagenic action of sodium lignogumate at mutations induction by mitomycin C in Allium-test - Шкарупа, В. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Cytogenetic effects of sodium lignogumate on genotoxity induced by mitomycin C in Allium-test were studied. Sodium lignogumate was tested at a concentration of 100 mg/l at the joint 72-hour exposure with mitomycin C. Analysis of the root meristem cells of Allium cepa L. seedlings was carried by ana-telophase method. It was found that sodium lignogumate had antimutagenic properties, reducing the frequency of mitomycin C induced chromosome aberrations by 64,51%. Complete elimination of multiaberrant cells was revealed. There was observed differential activity of the drug to reduce the frequency of chromosome aberrations of different types. The frequency of all types of "bridges" at the influence of sodium lignogumate reduced by 1.98 times, and the frequency of all types of fragments – by 8.03 times. There was revealed the complete elimination of double fragments (of chromosomal type), the frequency of single fragments (of chromatid type) decreased by 8.2 times. The effective elimination of multiaberrant cells and fragments indicates the presence of not only desmutagenіc but also other mechanisms of antimutagenic properties of sodium lignogumate. Therefore, multiple mechanisms were revealed for implementing antimutagenic properties of sodium lignogumate by mitomycin C induced mutagenesis in Allium-test.